Development of Lipid Nanoparticle Mediated Delivery Paradigms for Therapeutic In Vivo CRISPR Genome Editing - Glass, Zachary. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Qiaobing Xu.; Committee: David Kaplan, Feng Zhang, and Emmanuel Tzanakakis.; Keyword: Biomedical engineering.; CRISPR-Cas9-mediated genome editing technologies are poised to revolutionize the therapeutic treatment of a variety of diseases. For many diseases with a genetic etiology, current treatments can only manage the symptoms; the root cause of the disease can only be addressed at the genetic level. Therapeutic genome editing has been limited by the lack of safe, effective, and efficient delivery strategies. Often CRISPR-Cas9 genome editing machinery is delivered into the cell via a viral vector, however for safety considerations, a nonviral delivery route, such as delivery of Cas9 in a mRNA or protein format, would be preferrable. Lipid nanoparticles are a versatile and promising tool for in vivo delivery of biomacromolecules and are promising for the intracellular delivery of either Cas9 mRNA or protein to effect genome editing. The combinatorial lipidoid strategy allows for the rapid development of thousands of potential lipid nanoparticle drug carriers, which must then be optimized for each given application. The current work reflects the development and optimization of lipid nanoparticle-mediated delivery platforms for both Cas9 mRNA and protein, for a variety of applications. I have developed a safe and efficient lipid platform for the delivery of mRNA to the liver. I demonstrated the application of this platform by generating long-lasting, therapeutically relevant levels of genome editing in the liver upon a single administration of Cas9 mRNA co-delivered with a guide RNA targeting the Angptl3 gene, a gene relevant in cholesterol regulation that has been explored for the treatment of hyperlipidemia. I have also demonstrated intramuscular delivery of Cas9 protein to the gastrocnemius muscle in a mouse model of Duchenne Muscular Dystrophy, and have demonstrated some optimization of the lipid formulation to achieve more efficient genome editing in the muscle. I have also developed a platform to assist in more rapid screening of the combinatorial lipid library. Overall, this work reflects significant advancement in the development of non-viral CRISPR delivery platforms. More work will be necessary to continue to optimize the delivery paradigms, especially for Cas9 protein delivery. However this lays a significant foundation to develop these technologies, and ultimately allow their safe and effective therapeutic translation.